Introduction to women, gender, sexuality studies - Kang, Miliann; Lessard, Donovan; Heston, Laura; University of Massachusetts Amherst. Libraries; BC Open Textbook Project; BCcampus (University of Massachusetts Amherst Libraries, 2017)
"This textbook introduces key feminist concepts and analytical frameworks used in the interdisciplinary Women, Gender, Sexualities field. It unpacks the social construction of knowledge and categories of difference, processes and structures of power and inequality, with a focus on gendered labor in the global economy, and the historical development of feminist social movements. The book emphasizes feminist sociological approaches to analyzing structures of power, drawing heavily from empirical feminist research"--BCcampus website.
An Introduction to Women, Gender, Sexuality Studies: Grounding Theoretical Frameworks and Concepts -- Challenging Binary Systems and Constructions of Difference -- Institutions, Culture, and Structures -- Gender and Work in the Global Economy -- Historical and Contemporary Feminist Social Movements.
This work is licensed under the Creative Commons Attribution CC-BY.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Mode of access: World Wide Web.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Online version, 2017; title from PDF (viewed on August 28, 2017).
Keywords: Sex role -- Study and teaching; Women's studies